Synergetic effects of Clostridium butyricum and emodin on antioxidant capacities and immune‐related gene expression of the giant freshwater prawns (Macrobrachium rosenbergii) under ammonia stress. (10th January 2021) - Adisu Tadese, Dawit; Sun, Cunxin; Liu, Bo; Tamiru, Metekia; Song, Changyou; Takele, Lishan; Zhou, Zhigang; Xu, Hongqin
Abstract: This study aimed to investigate the synergetic effects of dietary emodin and Clostridium butyricum on antioxidant capacities and immune gene expression of freshwater prawn ( Macrobrachium rosenbergii ) under ammonia stress. Nine experimental diets were formulated with three emodin levels (0, 25 and 50 mg/kg) and three C . butyricum levels (0, 250 and 500 mg/kg, 2 × 107 CFU g −1 ) arranged in a 3 × 3 factorial design. Emodin dictated the relatively lower superoxide dismutase (SOD) activity after stress compared to before. Glutathione peroxidase (GPx) exhibited a significant difference among treatments fed emodin after ammonia exposure. Emodin and C . butyricum sparked the relatively lower malondialdehyde (MDA) levels before and after stress compared with the control. The expression of heat shock protein (HSP70) significantly augmented by emodin alone ( p  < 0.001) and in the interaction with C . butyricum ( p  < 0.01), while C . butyricum showed insignificant result before stress ( p  > 0.05) independently. After the ammonia challenge, the expression of HSP70 was significantly down‐regulated by the individual and synergetic effects of emodin and C . butyricum ( p  < 0.001). Toll gene expression was significantly increased by both emodin and C . butyricum before and after ammonia antagonism ( p  < 0.001). Similarly, dorsal gene expression was remarkably enhanced by emodin and C . butyricum before and after ammonia challenge ( p  < 0.01), and synergetic effects were observed before stress exposure ( p  < 0.05). The present study indicated that the synergetic effects of C . butyricum and emodin could significantly improve the antioxidant capacity, immune‐related gene expression and survival rate of M . rosenbergii under ammonia stress. The optimum combination of these components was 250 mg/kg (2x 107 CFUg −1 ) and 50 mg/ kg.